STRATEGI PENGMBANGAN OBJEK WISATA DI PANTAI PANJANG KOTA BENGKULU - Alga Miyanda (UM. Bengkulu, 2026)
Pantai Panjang has the main strength in the form of a vast and natural landscape, a strategic location in the center of Bengkulu City, easy accessibility, and its status as a regional tourism icon. In addition, the function of the area as an open public space and a center of community economic activity (local traders) is a significant social capital in the development of destinations. However, there are still several weaknesses, especially in terms of hygiene management, limited public facilities, non-optimal arrangement of traders, and cross-sector coordination that has not been fully integrated. These weaknesses have an impact on the quality of service and the comfort of visitors. Keyword: Attractions pantai panjang